2019
DOI: 10.3390/ijms20246307
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EYA3 Phosphorylation by Src Kinase Identifies Residues Involved in Cell Proliferation

Abstract: Eyes absent (EYA) are non-thiol-based protein tyrosine phosphatases (PTPs) that also have transcriptional co-activator functions. Their PTP activity is involved in various pathologies. Recently, we demonstrated that Src tyrosine kinase phosphorylates human EYA3 by controlling its subcellular localization. We also found EYA3 s ability to autodephosphorylate, while raising the question if the two opposing processes could be involved in maintaining a physiologically adequate level of phosphorylation. Using native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…This Abl -Eya signaling circuitry plays a role in the development of the Drosophila visual system. There is also some evidence that EYA3 has auto-dephosphorylation activity when over-expressed in HEK293T cells (Ionescu et al 2019). Whether tyrosine phosphorylation of EYA proteins affects its other biochemical activities (transactivation and putative threonine phosphatase) remains to be determined.…”
Section: Auto-dephosphorylation Of Eyasmentioning
confidence: 99%
See 2 more Smart Citations
“…This Abl -Eya signaling circuitry plays a role in the development of the Drosophila visual system. There is also some evidence that EYA3 has auto-dephosphorylation activity when over-expressed in HEK293T cells (Ionescu et al 2019). Whether tyrosine phosphorylation of EYA proteins affects its other biochemical activities (transactivation and putative threonine phosphatase) remains to be determined.…”
Section: Auto-dephosphorylation Of Eyasmentioning
confidence: 99%
“…Little is known thus far about cell-cycle associated fluctuations in EYA3 and EYA4 levels, but over-expression of EYA3 increases cell proliferation and this is linked to the phosphorylation of specific tyrosine residues in EYA3 (Ionescu et al 2019).…”
Section: Regulation Of Eya Ptp Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of EYAs is present in many tumor types, performing transcriptional cofactor and tyrosine phosphatase functions. Ionescu et al (2019) found that the upregulation of EYA3 has proliferative effects. MED12L is part of the Mediator complex, a multiprotein complex involved in transcription of RNA polymerase II-dependent genes.…”
Section: Enriched Pathway Analysismentioning
confidence: 99%
“…Phosphorylations usually introduce conformational changes that activate/inactivate the enzymatic activity of a protein, or simply prime degradation processes, like the ones involved in the yeast cell cycle (see, e.g., in [3,4] dealing with the degradation of Sic1 and Whi5, respectively) or those involving tyrosine kinase pathways, regulating diverse cellular processes, and whose dysregulation is one of the leading causes of cancer progression [5]. In many important cases, multi-site phosphorylations are required to ensure the correct timing of activation [6,7].…”
Section: Introductionmentioning
confidence: 99%